HUBUNGAN PERSEPSI KETIDAKSETARAAN GENDER DENGAN MOTIVASI BELAJAR IPS SISWA DI KELAS VIII SMP WIRAGUNA LIMBANGAN GARUT - Azizah Nuralifah, Icha; Mulyana, Eldi; Setiawan, Yana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between perceptions of gender inequality and the learning motivation of eighth-grade students in Social Studies (IPS) at SMP Wiraguna Limbangan Garut. The issue of gender equality in educational settings remains an important concern, as differences in treatment, perspectives, and stereotypes based on gender can influence students’ learning processes and motivation to participate in classroom activities. This study employed a descriptive qualitative approach, with data collected through in-depth interviews involving students, Social Studies teachers, and school counselors to obtain a comprehensive understanding of students’ perceptions of gender inequality within the school environment. The findings indicate that most students have a fairly good understanding of the concept of gender equality and perceive that the school has provided relatively equal opportunities for both male and female students in learning activities and other school-related programs. However, gender stereotypes were still identified, particularly in the distribution of group tasks, expectations regarding academic abilities, and perceptions of students’ characteristics based on gender. The study also found that fair treatment, an inclusive learning environment, and equal opportunities in the classroom contribute significantly to increasing students’ self-confidence, active participation, and learning motivation in Social Studies. Therefore, continuous efforts from the school are needed to strengthen gender-responsive education in order to create a more equitable learning environment and to support the optimal development of all students.